Neonatal hyperbilirubinemia: a critical appraisal of current guidelines and evidence - Francesco Raimondi; Teresa Ferrara; Angela Carla Borrelli; Daniela Schettino; Claudia Parrella; Letizia Capasso (Hygeia Press di Corridori Marinella, 2012)
The neurological damage of neonatal hyperbilirubinemia is often seen in developed countries as a remnant of a long gone past before the introduction of effective phototherapy and exchange transfusion. However, several reports in the past two decades from the United States have led to the institution of a Kernicterus National Registry. Similar reports from all over Western Europe have forced the pediatric national societies to issue specific guidelines on the clinical management of neonatal hyperbilirubinemia. The present paper reviews the highlights and pitfalls of the documents from Australia, Canada, New Zealand, India, Israel, Spain, Norway and South Africa.